2018
DOI: 10.1039/c7dt03637j
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(ii) arene NSAID complexes: inhibition of cyclooxygenase and antiproliferative activity against cancer cell lines

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are a group of molecules which have been found to be active against cancer cells with chemopreventive properties by targeting cyclooxygenase (COX-1 and COX-2) and lipoxygenase (LOX), commonly upregulated (particularly COX-2) in malignant tumors. Arene ruthenium(ii) complexes with a pseudo-octahedral coordination environment containing different ancillary ligands have shown remarkable activity against primary and metastatic tumors as reported earlier. This work des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 56 publications
2
60
0
Order By: Relevance
“…It is worth mentioning that the potential COX inhibition activity of the compounds discussed above was not studied. More recently, Mukhopadhyay et al (2018) reported a series of ruthenium(II) cymene complexes bearing different NSAID ligands, (13) (Figure 3), including diclofenac and ibuprofen, but also naproxen (Npx) and aspirin (Asp) [82]. Except for the Ru-Asp complex, which was found inactive against MCF7 cells, all complexes displayed a lower IC 50 value (<0.1 µM) than their corresponding free NSAID (>80 µM) in this cell line.…”
Section: Other Ruthenium Complexes For the Treatment Of Hormone Recepmentioning
confidence: 99%
“…It is worth mentioning that the potential COX inhibition activity of the compounds discussed above was not studied. More recently, Mukhopadhyay et al (2018) reported a series of ruthenium(II) cymene complexes bearing different NSAID ligands, (13) (Figure 3), including diclofenac and ibuprofen, but also naproxen (Npx) and aspirin (Asp) [82]. Except for the Ru-Asp complex, which was found inactive against MCF7 cells, all complexes displayed a lower IC 50 value (<0.1 µM) than their corresponding free NSAID (>80 µM) in this cell line.…”
Section: Other Ruthenium Complexes For the Treatment Of Hormone Recepmentioning
confidence: 99%
“…Thus, the main problem of these kinds of Ru II /η 6 -arene/carboxylate complexes can be their low stability in coordinating solvents or physiological medium, limiting their biological application. 37,38 Benzoic acid and its analogs belong to an important class of ligands, displaying a structural diversity, allowing them to access the ortho, meta and para positions with a wide possibility of substitution with many organic functions. Due to the promising chemical and biological results obtained with the Ru II /η 6 -arene-based complexes, this paper reports on the reactivity of p-substituted benzoic acid derivatives with Ru II /η 6 -arene/triphenylphosphine complexes with general formula [Ru(η 6…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of silver(I), gold(I), and zinc (II) complexes with ibuprofen for antibacterial activities. Also, a platinum (II)/(IV), Ru (II), Cu (II) complexes with ibuprofen have been reported as anticancer drugs . Recently, we also have reported the antioxidant activity of copper (II) complexes of ibuprofen amide‐phenanthroline and cyclometalated ruthenium (II) complex containing ibuprofen for inhibition of cyclooxygenase and in vitro cytotoxicity activities .…”
Section: Introductionmentioning
confidence: 99%